Aflatoxins and fumonisins contamination of home-made food (weanimix) from cereal-legume blends for children - Kumi, J.; Mitchell, M.J.; Asare, G.A.; Dotse, E.; Kwaa, F.; Phillips, T.D.; Ankrah, N.-A. (Ghana medical journal, 2014)
BACKGROUND: Weanimix is an important food for children in Ghana. Mothers are trained to prepare homemade weanimix from beans, groundnuts and maize for their infants. Groundnuts and maize are prone to aflatoxin contamination while fumonisin contaminates maize. Aflatoxin, is produced by the Asperguillus fungi while fumonisin, is produced by Fusarium fungi. These mycotoxins occur in tropical areas worldwide due to favorable climate for their growth.OBJECTIVE: The objective of the study was to determine the levels of aflatoxin and fumonisin in homemade weanimix in the Ejura-Sekyedumase district in the Ashanti Region of Ghana.METHODS: Thirty six homemade weanimix samples (50g each) were collected from households. Aflatoxin and fumonisin were measured using a fluorometric procedure described by the Association of Official Analytical Chemist (AOAC official method 993.31, V1 series 4).RESULTS: Aflatoxin and fumonisin were detected in all 36 samples, range 7.9-500ppb. Fumonisin levels range: 0.74-11.0ppm). Thirty (83.3%) of the thirty six samples were over the action limit of 20ppb for aflatoxin with an overall mean of 145.2 ppb whiles 58.3% of the samples had fumonisins above the action limit of 4 ppm with an overall mean of 4.7 ppm.CONCLUSION: There were significant aflatoxin and fumonisin contamination of homemade weanimix. Children fed on this nutritional food were being exposed to unacceptable levels of aflatoxin and fumonisin. Therefore there is a critical need to educate mothers on the dangers of mycotoxin exposure and to develop strategies to eliminate exposure of children fed homemade weanimix to aflatoxin and fumonisin.
Keywords: Aflatoxin; Fumonisin; Home-made Weanimix; infants